2018
DOI: 10.1155/2018/2381296
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment with Cord Blood Serum in Glaucoma Patients: A Preliminary Report

Abstract: Purpose To report data which happened to be observed in two glaucoma patients treated with Cord Blood Serum (CBS) eye drops. Design A case report and retrospective data analysis. Methods CBS topical eye drops, characterized in advance for growth factors (GFs) content, were administered for two months with the aim to relieve their subjective symptoms, in two patients who had referred ocular surface discomfort, although in absence of any sign of keratopathy. As patients were also affected by advanced glaucoma at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Microglia activation leads to neuroinflammation and the progression of neurodegenerative events. Recently a paper published from our group [13] reports a preliminary observation on two glaucomatous patients, which supports our hypothesis of successful therapy with CBS. The unifying pathophysiology characteristics between glaucoma and AMD are the activation of neuroinflammatory events, which are responsible for the progression of both diseases.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Microglia activation leads to neuroinflammation and the progression of neurodegenerative events. Recently a paper published from our group [13] reports a preliminary observation on two glaucomatous patients, which supports our hypothesis of successful therapy with CBS. The unifying pathophysiology characteristics between glaucoma and AMD are the activation of neuroinflammatory events, which are responsible for the progression of both diseases.…”
Section: Discussionsupporting
confidence: 82%
“…The possibility exists that according to differential contents of factors, we might select eye drops with targeted efficacy to different neurodegenerative processes and stages of the disease. Clinical observation in glaucoma patients [13] seems to support this hypothesis. Here we report preliminary data showing that treatment with CBS-based eye drops can ameliorate the retinal damage induced by exposure to high-intensity light.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…medium also meliorates the inflammatory activation, crucial mechanism responsible of the neurodegenerative diseases. These data can offer interesting cues for neuroprotection studies, supporting the results obtained both in animal model [14,15,17] and patients [33], where BDNF and NGF-based eye drops have been tested with beneficial effects on visual field. The survival and protective functions of neurotrophins are mediated by the signaling cascade activated by the Trk receptor.…”
Section: Plos Onesupporting
confidence: 78%
“…A preliminary study that analyzed the effect of UCBS topically administered to glaucoma patients observed positive results, as shown by improvements in visual field test parameters. This efficacy is thought to be related to the high growth factor content of the serum, which potentially exerts a neuroprotective action on the optic nerve [45]. However, the authors stated that the incidentally observed amelioration in these glaucoma patients requires further investigation.…”
Section: Ucbsmentioning
confidence: 99%